2013
DOI: 10.3109/21678421.2013.799700
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fatigue and psychosocial variables on quality of life for patients with motor neuron disease

Abstract: Our objective was to evaluate the direct and indirect relationships between psychosocial variables, fatigue and quality of life for patients with motor neuron disease (MND). A cross-sectional sample of 147 MND patients was recruited from five neurological care centres in England. Variables included anxiety, coping, depression, fatigue, functional status, social withdrawal and quality of life. Direct and indirect relationships between study variables were assessed using structural equation modelling (SEM), usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 31 publications
2
70
2
Order By: Relevance
“…Our findings are consistent with those reported by Bookwala and Lawson,11 who found that poorer self-reported vision in older adults was associated with lower psychological functioning indirectly through activity limitation and social isolation. In a clinical study of patients with visual field defects from optic neuropathies, activity limitation mediated the relationship between objectively measured remaining visual field and psychological functioning 32.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings are consistent with those reported by Bookwala and Lawson,11 who found that poorer self-reported vision in older adults was associated with lower psychological functioning indirectly through activity limitation and social isolation. In a clinical study of patients with visual field defects from optic neuropathies, activity limitation mediated the relationship between objectively measured remaining visual field and psychological functioning 32.…”
Section: Discussionsupporting
confidence: 93%
“…Items were generated from a literature review,17 20 focus groups and semistructured interviews with patients with DR,6 and semistructured interviews with diabetes or ophthalmic experts, and were revised following cognitive interviews with patients with DR 16. We did not include objective measures of DR-related VI, such as VA, in our models as our self-reported measure of visual symptoms includes aspects of visual function beyond VA, such as difficulty with contrast and colour sensitivity and peripheral vision, and subjective visual symptomology has been more closely associated with QoL outcomes 11. The characteristics of the nine QoL domains are provided in table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations